2020
DOI: 10.1002/jmv.25985
|View full text |Cite
|
Sign up to set email alerts
|

The anti‐HIV drug nelfinavir mesylate (Viracept) is a potent inhibitor of cell fusion caused by the SARSCoV‐2 spike (S) glycoprotein warranting further evaluation as an antiviral against COVID‐19 infections

Abstract: Severe acute respiratory syndrome coronavirus-2 (SARS CoV-2) is the causative agent of the coronavirus disease-2019 (COVID-19) pandemic. Coronaviruses enter cells via fusion of the viral envelope with the plasma membrane and/or via fusion of the viral envelope with endosomal membranes after virion endocytosis. The spike (S) glycoprotein is a major determinant of virus infectivity. Herein, we show that the transient expression of the SARS CoV-2 S glycoprotein in Vero cells caused extensive cell fusion (formatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
130
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(142 citation statements)
references
References 44 publications
6
130
0
2
Order By: Relevance
“…Nel navir in WT spike protein was placed in the HR1 region and formed hydrogens bond with K310, I312, and Q314, and hydrophobic interactions with L303, E309, G311, Y313, I664, P665 and I666 as previously reported (Fig. 7L) 31 . While Nel navir with D614 mutant was also placed on the HR1 region but interacted with some different residues than in the wild type, formed a hydrogen bond with N317, S596, K947 and Q1010 and hydrophobic interactions with Q314, F592, G593, I1013 (Fig.…”
Section: Molecular Docking With Known Ligandssupporting
confidence: 67%
See 3 more Smart Citations
“…Nel navir in WT spike protein was placed in the HR1 region and formed hydrogens bond with K310, I312, and Q314, and hydrophobic interactions with L303, E309, G311, Y313, I664, P665 and I666 as previously reported (Fig. 7L) 31 . While Nel navir with D614 mutant was also placed on the HR1 region but interacted with some different residues than in the wild type, formed a hydrogen bond with N317, S596, K947 and Q1010 and hydrophobic interactions with Q314, F592, G593, I1013 (Fig.…”
Section: Molecular Docking With Known Ligandssupporting
confidence: 67%
“…Finally, to explore how these punctual mutations affect the protein-ligand binding, a molecular docking with Cepharenthine, Hydroxychloroquine, and Nel navir which are experimental reported spike ligands were performed [29][30][31] Cepharanthine showed potent antiviral activity In vitro against SARS-CoV-2, and by molecular docking, spike protein was suggested as its target. It is suggested that cepharanthine is bound to RBD, and might interfere with human ACE2 binding avoiding the anchorage of the virus to the cell 30,35 .…”
Section: Molecular Docking With Known Ligandsmentioning
confidence: 99%
See 2 more Smart Citations
“…A cell-based study in inhibiting the SARS-CoV-2 entry indicated a 1 µM EC50 value. 26,27 However, our IC50 determination against M Pro resulted in a value of 234 ± 5 µM, highlighting that nelfivavir likely inhibits another key SARS-CoV-2 enzyme or protein or interferes with key cellular processes that are required for the SARS-CoV-2 entry into host cells. These possibilities need to be studied further.…”
Section: Resultsmentioning
confidence: 93%